Issues of Retraining and Professional Development of Pedagogical Personnel - o’g’li, Egamberdiyev Oyatillokh Alisher; qizi, Sotvoldiyeva Orzigul Marufjon; qizi, Rasulova Hidoyat Rasuljon (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the training and retraining of Personnel is aimed at updating and deepening the professional knowledge and skills of specialists. The procedure and periodicity of training and retraining of personnel shall be determined by the relevant ministry office. With the legislation, the requirements for professional development and retraining of representatives of certain spheres can be established. Opinions and comments on the submission of a certificate or certificate of the sample approved by the state according to the results of the study in educational institutions of professional development and retraining of personnel are made.